2003
DOI: 10.1007/bf03006677
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibroma with increased uptake of [F-18]-fluoro-2 deoxy-d-glucose interpreted as a metastatic lesion

Abstract: We report a patient with a solitary spinal neurofibroma in the posterior mediastinum interpreted as a metastatic tumor. A 46-year-old female with rectal cancer who had undergone operation and subsequent adjuvant chemotherapy two years previously was referred to our department for a follow-up whole body FDG-PET study. PET scan revealed a mass with increased uptake of FDG (SUV = 4.6) in the posterior mediastinum. MRI examination showed a dumbbell neurogenic tumor originating from the intercostal nerve at T6 leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Moreover, the gliosis in the avulsed roots also contributes to higher FDG uptake. This result was supported by previous studies, which demonstrated increased uptake of FDG through PET in the neurofibroma of peripheral nerves [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the gliosis in the avulsed roots also contributes to higher FDG uptake. This result was supported by previous studies, which demonstrated increased uptake of FDG through PET in the neurofibroma of peripheral nerves [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 89%
“…With use of an SUV of 2.5 as a cutoff value, they were able to differentiate between malignant and benign neurogenic tumors (61). However, other investigators have reported an overlap between benign and malignant lesions with respect to FDG uptake (62,63).…”
Section: Discussionmentioning
confidence: 98%
“…The overall risk of cancer in NF1 patients is 2.7 times higher than the general population with the most common neoplasms originating from connective tissue or the central nervous system (CNS); however, there is no greater risk of cancer at other sites [2]. Perhaps, it is not surprising then that we could identify only one other case in the English literature in which PET was used to distinguish metastatic carcinoma from a benign neurofibroma [3]. In this case, a 46-year-old female with a past history of early stage rectal cancer presented with a posterior mediastinal mass.…”
Section: Discussionmentioning
confidence: 92%